Health Promotion Cucumber Juice on Reduction of High Blood Pressure in Hypertensive Patients Pregnant Women and Maternity Mothers at Aek Haruya Village - Riska Yanti; Ramadhani Nainggolan; Melia Shintia Mutiara Pohan (CV. Creative Tugu Pena, 2024)
Hypertension in pregnancy is a major cause of maternal morbidity and mortality. One of the non-pharmacological treatments that can be given to people with high blood pressure is dietary treatment. This can be done by eating vegetables that can affect blood pressure, such as cucumber (Cucumis Sativus L.). Cucumber has hypotensive (lowers blood pressure) properties. The contents of cucumbers can help lower blood pressure because cucumbers contain potassium, magnesium and phosphorus, which are effective in the treatment of hypertension. The aim of this activity is to inform pregnant women and mothers-to-be about one of the non-pharmacological ways of reducing hypertension that can occur during pregnancy, namely by drinking cucumber juice. The methods used were lectures and question and answer sessions. This programme was conducted in August 2024 with 20 pregnant women in Aek Haruaya village as respondents. The results of the community service were an average pre-test score of 50 points and an average post-test score of 70 points, there was an increase in the knowledge of pregnant women about giving cucumber juice to reduce hypertension with an average increase of 20 points. It is hoped that education will increase pregnant women's knowledge of non-pharmacological efforts to reduce hypertension, which can occur during pregnancy.